2016
DOI: 10.14202/ijoh.2016.69-74
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of extended spectrum beta-lactamases-producing strains belonging to cefotaxime-M-1 class from intensive care units patients and environmental surfaces in Pakistan

Abstract: Aim:The emergence of multidrug-resistant (MDR) bacteria is the most dangerous threat for the treatment of infectious diseases. The aim of this study was to detect and characterize extended spectrum beta-lactamases (ESBLs) and carbapenemaseproducing Klebsiella pneumoniae and Escherichia coli among patients and environment of intensive care units (ICUs) of three tertiary care hospitals in Pakistan. Materials and Methods:A total of 82 samples from ICU's patients and inanimate environment (injection trays, wash ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Additionally, a study conducted in the recent past found ESBL producing K. pneumoniae with a rate of 15.8% ( Bukhari et al, 2016 ), the low percentage prevalence may be due to the small sampling fraction and a huge diversity of sample sources as compared to our studied samples. Worryingly, a significant percentage prevalence (32%) of carbapenem-resistant K. pneumoniae has also been detected in the present study.…”
Section: Discussionmentioning
confidence: 74%
“…Additionally, a study conducted in the recent past found ESBL producing K. pneumoniae with a rate of 15.8% ( Bukhari et al, 2016 ), the low percentage prevalence may be due to the small sampling fraction and a huge diversity of sample sources as compared to our studied samples. Worryingly, a significant percentage prevalence (32%) of carbapenem-resistant K. pneumoniae has also been detected in the present study.…”
Section: Discussionmentioning
confidence: 74%
“…In our study, ESBL producing Enterobacteriaceae were isolated in 16 of the 65 (24.6%) environmental samples. In published reports, the percentage of inanimate hospital environments contaminated with ESBL are signi cantly varied ranging from 3% to 33% of surfaces in patients' rooms on regular hospitals wards, as reported from Gonder in Ethiopia (14.8%) [6], Tunisia (4%) [11], Israel (9%) [20], Tunisia (4%) [5], UK (3.1%) [12] and Pakistan (33%) [2]. These discrepancies could possibly be due to differences in patient colonization load, hospital's cleaning/disinfection protocols, study design including timing of sample collection and laboratory method used [5,11,20,21].…”
Section: Discussionmentioning
confidence: 99%
“…In Gram-negative bacteria, β-lactamase production remains the most important mechanism of resistance to β-lactam group of antibiotics and has become a global challenge in infection control. One group of these enzymes is called extended-spectrum β-lactamases (ESBLs) [1][2][3]. ESBLs hydrolyze a wide range of cephalosporins including the oxyimino group of cephalosporins such as ceftriaxone, ceftazidime, cefotaxime and the monobactam drugs such as aztreonam, but do not hydrolyze cephamycins and carbapenems, and their activity is inhibited by clavulanic acid [3,4].…”
Section: Introductionmentioning
confidence: 99%